Análisis jurídico y doctrinario la prisión del alimentante por falta de pago en pensiones alimenticias - Teran Quinaucho, Juan Carlos (2016)
The thesis presented below tends to show there are inconsistencies and arbitrariness in terms of application of article 141 the Organic Code of the Child and Adolescents, regarding the responsibility subsidiary obligation facing processes food. Both theoretical work and the field, reflect the problem and the discontent of the citizenry to the unnumbered provisions of Article 5 of the Reform Act Title V of Book II of the Code of Children and Adolescence for its inconsistencies and lack of analysis, regarding the selection, consideration, responsibility and negative consequences they face the subsidiary required. In the field research is demonstrated through surveys, interviews and case studies, which makes failure to reform the unnumbered Article 5 of Law Amending Title V of Book II of the Code of Children and adolescents because their application is enormously damaging to all who are being considered subsidiary obligations, especially who unites the bond of consanguinity with the that has custody of the child, since no but simply looks at the objective circumstances that the obligation must be fulfilled, although this sweep away the means to oppose its purpose. After gathering around the theoretical and empirical research problem, I could verify the objectives and the hypothesis raised in the thesis project, which made regarding the need for amend Article 5 of the unnumbered Reform Act Title V of Book II of the Code of Children and Adolescents with the aim of which is not considered to grandparents as required in relation to subsidiary brothers and uncles take into account certain circumstances such as economic status, status current studies and the number of children they have. For these reasons it has been determined conclusively the problem exists in the social, economic legal and within the application of the provisions of Unnumbered Section 5 of the Reform Act Title V of the Book II of the Code of Childhood and Adolescence and hence the urgent need of society legal reforms urgently needed under this law in such a way as to eliminate grandparents forced consideration of subsidiary, is considered with respect to other subsidiary required the circumstances specified in above, the State is considered as another the subsidiary and also required the establishment in against the principal propose actions possible and which will achieve compliance pension payments of foods in the child's and finally change the Code of Children and Adolescence equality with the consequences faced by both principals and subsidiary so that it exists and is fulfilled in benefit society as a whole guarantees all constitutional and legal certainty